The role of verbal and pictorial information in multimodal incidental acquisition of foreign language vocabulary - Bisson, Marie-Josée; van Heuven, Walter J.B.; Conklin, Kathy; Tunney, Richard J. (Taylor & Francis, 2014)
This study used eye tracking to investigate the allocation of attention to multimodal stimuli during an incidental learning situation, as well as its impact on subsequent explicit learning. Participants were exposed to foreign language (FL) auditory words on their own, in conjunction with written native language (NL) translations, or with both written NL translations and pictures. Incidental acquisition of FL words was assessed the following day through an explicit learning task where participants learned to recognize translation equivalents, as well as one week later through recall and translation recognition tests. Results showed higher accuracy scores in the explicit learning task for FL words presented with meaning during incidental learning, whether written meaning or both written meaning and picture, than for FL words presented auditorily only. However, participants recalled significantly more FL words after a week delay if they had been presented with a picture during incidental learning. In addition, the time spent looking at the pictures during incidental learning significantly predicted recognition and recall scores one week later. Overall, results demonstrated the impact of exposure to multimodal stimuli on subsequent explicit learning, as well as the important role that pictorial information can play in incidental vocabulary acquisition.